Determinan Faktor yang Berpengaruh terhadap Penggunaan E-Filing pada Masa Pandemi Covid-19 - Ahmad Try Handoko; Nanda Ladepi (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
E-filing is a modernization of the tax system which aims to make it easier for Individual Taxpayers (WPOP) to report their Annual SPT. In the midst of the current pandemic conditions, where people are required to work from home, e-filing has become the main solution in submitting the 2022 Individual Annual Tax Return. However, the percentage of e-filing use during the Covid-19 period has still not reached 100% . The aim of this research is to analyze the determinants of factors that influence the acceptance of the e-filing system, especially during the Covid-19 pandemic, using technology acceptance model 3 (TAM 3). The research method used is a quantitative approach, using a survey method via a questionnaire which is then processed using a structural equation model (SEM) with the help of SmartPLS3 software. The research results show that the intention to use e-filing is the main factor in accepting the e-filing system. WPOP's intention to use e-filing is influenced by factors such as usability of e-filing, ease of use of e-filing and subjective norms. It is hoped that the results of this research can be taken into consideration by the Directorate General of Taxes (DJP) to maximize the socialization of the use of the e-filing system, so that in the future SPT reporting can be done completely online via e-filing.